DECISION ANALYSIS OF BUYING HERBAL TEA FROM FEED PLANTS TELANG FLOWER (Clitoria ternatea) (Case Study On Clitea Student Innovation Products) - I. A. G. D., Manuaba; Putri, B. R. T.; Inggriati, N. W. T. (Jurnal Peternakan Tropika, 2023)
This study aims to determine consumers' purchasing decisions for Clitea herbal tea products at Denpasar and Badung areas based on various factors such as product quality, price, social environmental and service quality. This study used 75 respondents, were selected using multistage sampling method. This study used are primary data and secondary data. The Research starts from March to May 2022. Data in this study wer analyzed using descriptive analysis of percentage. From the analysis results show that the most influential factors are 1) Service quality factor as much as 70.7% of respondents stated it was important, 2) Followed by the price factor as much as 66.7%. 3) Then the quality factor is 66.2%. 4) And the last is the social environment factor as much as 62.2%. The most influenced on purchasing decisions is service quality factor